Preparation of new doxycycline monohydrate polymorphs by ultrasonication enhanced supercritical antisolvent recrystallization process - Snehashis Nandi; Miguel A. Rodrigues; Andreia Duarte; Teresa G. Nunes; Luis Padrela (Journal of CO2 Utilization)
Polymorphism is a crucial factor in the pharmaceutical industry, as different polymorphs can display different physicochemical properties, including stability, solubility, and/or bioavailability. The ultrasonication-enhanced supercritical antisolvent recrystallization (UE-SAR) process is a novel investigated approach for producing novel polymorphs.This work aimed to generate and characterize doxycycline monohydrate (DOXY·H2O forms II, III, and IV) polymorphs produced from suspensions of its as received form (DOXY·H2O form I) using the UE-SAR process. A two-stage Design of Experiments (DoE) analysis was performed to assess the impact of various processing parameters such as ultrasonication, pressure, temperature, and residence time on the polymorphic outcome in each experimental run. The solid state characterization revealed that the produced polymorphs (DOXY·H2O form II, DOXY·H2O form III) have distinct powder X-ray diffraction (PXRD), Raman, Fourier Transform Infrared (FTIR) patterns and higher thermal stability. Moreover, the structures of DOXY·H2O forms I and II were further elucidated by solid state nuclear magnetic resonance (SS NMR) from 13 C and 15 N cross polarization (CP) and magic angle spinning (MAS) spectra. Overall, the results from this work highlight that use US-SAR method can induce the formation of different supramolecular structures in tetracyclines when they are suspended in a supercritical phase, and polymorphic purity can be enhanced by prolonged ultrasonication.